Thermal-Mechanical Coupled Manufacturing Simulation in Heterogeneous Materials - El Amri, Abdelouahid; El Yakhloufi Haddou, M.; Khamlichi, A. (Salehan Institute of Higher Education, 2016)
This work is aimed to investigate on thermal and thermo-mechanical behaviour of 6061 Aluminium alloy. The main target of the present investigation is to apply a numerical procedure to assess the thermo-mechanical damage. Finite element analyses of the notched tensile specimens at high temperature have been carried out using ABAQUS Software. The objective was to study the combined effects of thermal and mechanical loads on the strength and ductility of the material. The performance of the proposed model is in general good and it is believed that the presented results and experimental–numerical calibration procedure can be used in practical finite-element simulation.